147k views
0 votes
- 2(3s - 5) – 10 = - 2(6s + 8) - 3

User Amir Keibi
by
5.3k points

1 Answer

4 votes

ANSWER:

-3.167

Step-by-step explanation:

Given:

-2(3s - 5) – 10 = -2(6s + 8) - 3

To solve this, first expand the parentheses on both sides of the equation using distributive property:

-2(3s) - 2(-5) - 10 = -2(6s) - 2(8) - 3

-6s + 10 - 10 = -12s - 16 - 3

Collect like terms:

-6s + 12s = -16 - 3 - 10 + 10

6s = -19

Divide both sides by 6:

6s/6 = -19/6


(6s)/(6)\text{ = }(-19)/(6)
s\text{ = }-3.167

User Lurr
by
5.7k points